Andragogy and training of entrepreneurs at UNESR Bolívar - Doubront, Marcel (2019)
Given the complex crisis experienced by Venezuela, which has provoked a systematic defection of university students, there is a need to structure a training plan for entrepreneurs, to create new businesses, where youth have a leading role, strengthening a culture of entrepreneurship compatible with Andragogical, participatory and flexible philosophy of Universidad Nacional Experimental Simón Rodríguez (UNESR).